A bacterial Ras-like small GTP-binding protein and its cognate GAP establish a dynamic spatial polarity axis to control directed motility. - Yong Zhang (Public Library of Science (PLoS), 2010)
Regulated cell polarity is central to many cellular processes. We investigated the mechanisms that govern the rapid switching of cell polarity (reversals) during motility of the bacterium Myxococcus xanthus. Cellular reversals are mediated by pole-to-pole oscillations of motility proteins and the frequency of the oscillations is under the control of the Frz chemosensory system. However, the molecular mechanism that creates dynamic polarity remained to be characterized. In this work, we establish that polarization is regulated by the GTP cycle of a Ras-like GTPase, MglA. We initially sought an MglA regulator and purified a protein, MglB, which was found to activate GTP hydrolysis by MglA. Using live fluorescence microscopy, we show that MglA and MglB localize at opposite poles and oscillate oppositely when cells reverse. In absence of MglB, MglA-YFP accumulates at the lagging cell end, leading to a strikingly aberrant reversal cycle. Spatial control of MglA is achieved through the GAP activity of MglB because an MglA mutant that cannot hydrolyze GTP accumulates at the lagging cell end, despite the presence of MglB. Genetic and cell biological studies show that the MglA-GTP cycle controls dynamic polarity and the reversal switch. The study supports a model wherein a chemosensory signal transduction system (Frz) activates reversals by relieving a spatial inhibition at the back pole of the cells: reversals are allowed by Frz-activated switching of MglB to the opposite pole, allowing MglA-GTP to accumulate at the back of the cells and create the polarity switch. In summary, our results provide insight into how bacteria regulate their polarity dynamically, revealing unsuspected conserved regulations with eukaryots.